Evaluating the effectiveness of hermetic grain storage bags for kocho production in two agro-ecologies of Gera district, Ethiopia - Zeleke Tesfahun Demissie; Kumela Dibaba Tolera; Chala G. Kuyu (Discover Food)
Abstract Kocho, a fermented food derived from enset (Ensete ventricosum), is a staple food consumed by millions in Ethiopia. Traditional enset fermentation methods for kocho production are labor-intensive, unhygienic, and often yield poor-quality kocho. This study evaluated enset processing practices and the effect of hermetic grain storage bags on the quality of fermented kocho in the Gera district of Ethiopia. A preliminary survey involving 132 respondents utilized a multistage random sampling approach was conducted to collect primary data on traditional fermentation techniques, fermentation duration, starter culture usage, and perceived advantages and disadvantages of current practices. The community is aware of several quality and safety issues related to traditional enset fermentation, including contamination risks from soil microorganisms, hygiene concerns, inconsistent product quality, and the labor-intensive nature of the process. However, there are additional issues that not be fully recognized, such as the nutritional degradation that can occur during prolonged fermentation, the effect of specific fermentation conditions on product quality and safety. The effectiviness of hermetic grain storage bags for kocho fermentation was evaluated using three hermetic grain storage bags (PICS, Agro Z, Grain pro) and conventional pits (using earthen pits for enset fermentation) as a fermentation method at two different altitude levels (high and medium altitude). Result indicates that the quality of kocho fermented in hermetic bags (PICS and Agro Z) significantly outperformed those produced using conventional methods. Specifically, kocho from PICS bags at high altitude exhibited the highest moisture content (82.28%), while traditional pits at mid-altitude had the lowest (71.26%). Protein content was notably higher in PICS bags (5.76% at high altitude), and fiber content was lower (2.07% at mid-altitude), indicating a more desirable texture. The ash content ranged from 3.12% to 3.79%, with significant differences based on fermentation method. Additionally, the pH of kocho samples varied, with the highest value (4.42) in PICS bags, and titratable acidity was significantly lower in hermetically fermented samples. Sensory evaluation further revealed that kocho bread from hermetic bags received higher acceptance scores for flavor, color, and overall quality compared to that from traditional pits, underscoring the enhanced quality and safety of kocho produced using improved fermentation methods. The use of hermetic grain storage bags, particularly PICS and Agro Z, is recommended for smallholder farmers to improve the quality of kocho production, thereby contributing to food security in Ethiopia. The findings not only demonstrate a viable alternative to traditional fermentation but also highlight the potential of hermetic storage technologies to enhance food safety, reduce post-harvest losses, and improve the resilience of agricultural practices, thereby contributing meaningfully to food security in Ethiopia.